How Transformational Leadership and Organizational Climate Drive Employee Performance: Evidence from a Public Organization - Naina Zahra Maulida; Akil; Achmad Taufik Ismail (Journal of Educational Management Research, 2026)
This study aims to examine the influence of transformational leadership and organizational climate on employee performance within a public service institution. A quantitative approach with a survey method was employed, involving 85 employees selected using a saturated sampling technique. Data were analyzed using multiple linear regression to determine the partial and simultaneous effects of the independent variables on employee performance. The findings indicate that transformational leadership has a positive and significant effect on employee performance with a moderate level of influence, while organizational climate shows a positive and significant effect with a stronger level of influence. Simultaneously, both variables significantly influence employee performance, with organizational climate having a more dominant contribution than transformational leadership. These results imply that strengthening a supportive and conducive organizational climate should be prioritized to improve employee performance. In addition, leaders need to enhance individualized consideration to ensure fair, inclusive, and sustainable engagement across all employees.